2015
DOI: 10.3945/jn.114.203604
|View full text |Cite|
|
Sign up to set email alerts
|

Poor Thiamin and Riboflavin Status Is Common among Women of Childbearing Age in Rural and Urban Cambodia ,

Abstract: Suboptimal status of both thiamin and riboflavin were common in Cambodian women, with substantially higher rates among women living in rural Prey Veng than in urban Phnom Penh. Strategies may be needed to improve the thiamin and riboflavin status of women in Cambodia. The unexpected finding of high riboflavin inadequacy status in Vancouver women warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Whitfield et al () reported that 82% of women ( n = 156) surveyed in Prey Veng, Cambodia, had biochemical evidence of low riboflavin status. Thus, interventions that result in a lower prevalence of inadequate riboflavin intake, as was found in the present study following intervention with EHFP plus aquaculture, are likely to improve nutrient status.…”
Section: Discussionmentioning
confidence: 99%
“…Whitfield et al () reported that 82% of women ( n = 156) surveyed in Prey Veng, Cambodia, had biochemical evidence of low riboflavin status. Thus, interventions that result in a lower prevalence of inadequate riboflavin intake, as was found in the present study following intervention with EHFP plus aquaculture, are likely to improve nutrient status.…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin deficiency is prevalent in many regions over the world, particularly in underdeveloped countries with a low intake of dairy products and meats5678. In the clinical conditions, patients with certain types of cancers and congenital heart disease, as well as those with excessive alcohol intake, are at a greater risk of riboflavin deficiency9.…”
mentioning
confidence: 99%
“…A recent study in Cambodia found 50% of the women subjects in Phnom Penh and rural Cambodia were thiamine deficient (39% urban, 59% rural) [15]. In developed countries, thiamine deficiency and beriberi are rare on a population basis, but clinical deficiencies are reported worldwide [16].…”
Section: "Conflicts" Of Evidencementioning
confidence: 99%